ANALYSIS OF THE NEWS CONCERNING THE ROMA MINORITY IN BULGARIA - Bahar Ayaz (Selçuk İletişim)
In this study news discourses dealing with the Roma minority in Bulgaria are analyzed. One of the most problematic issues facing Bulgaria in terms of the EU membership process was its attitude toward minorities. The government implemented several policies in this regard and was finally accepted as a member. The overall situation of the Roma minority has improved over time, but has the perceptions of society and the attitude of the media also changed with regard to minorities? This study is seeking answers to these questions. Media discourse plays an important role concerning the determination and maintenance of dominant ideas. Therefore this study mainly focuses on the news discourse related to the Roma minority. As a result it is observed that the news discourse maintains the current prejudices and ideologies about the Roma minority. In news items, the Roma minority are represented as marginal or different people who reside in illegal settlements, people who are more tolerant of violence, and people who need to be protected.